Angiographic patency of streptokinase in STEMI patients: smokers vs. non-smokers - Hirapur, Iranna; Setty, Srinivas; Rajendran, Ravindran; Nanjappa, Manjunath (International Journal of Research in Medical Sciences, 2018)
Background: Acute coronary syndrome is one of the leading causes of death. Smoking is known to be associated with many influencing factors for accelerating Myocardial Infarction (MI). In a country like India, Streptokinase (SK) is used as a leading therapeutic option for the treatment of ST elevation myocardial Infarction (STEMI). SK combines with plasminogen; this SK-plasminogen complex is responsible for fibrinolysis. The aim of this study was to determine angiographic patency after SK infusion in STEMI patients and comparison between smokers and non-smokers. Methods: In this observational, prospective and single-centre study conducted between September 2011 and April 2012, a total of 398 patients who were diagnosed with STEMI were included. Patients were divided in two groups i.e. smokers and non-smokers. The patients were treated with thrombolytic (streptokinase) therapy and evaluated for TIMI 3 flow by performing angiography within 72hours of thrombolysis with SK. Results: Of total 398 patients, 348 (87.4%) were male. The ratio of non-smokers and smokers was 1:2. Smokers were younger than the non-smokers (48.8±10.2 vs. 54.57±9.51). Post thrombolytic therapy, patients were evaluated for TIMI flow grades. Total of 202 patients achieved TIMI 3 flow, of which 157 were smokers and 45 were non-smokers. Conclusions: Smokers have relatively hypercoagulable state than non-smokers. Better outcome in smokers group may be because of younger age and lesser comorbidities. Smokers should be motivated and guided properly to quit smoking.